Microstructural Analysis and Constitutive Modeling of Superplastic Deformation Behavior of Al-Mg-Zn-Cu-Zr-xNi Alloys with Different Ni Contents - Zarnigor S. Turaeva; Ahmed O. Mosleh; Olga A. Yakovtseva; Anton D. Kotov; Anastasia V. Mikhaylovskaya (Metals)
Superplastic forming is a process that enables the production of complex-shaped parts using metallic alloys. To design the optimal forming regimes and ensure the success of forming operations, it is essential to use mathematical models that accurately represent the superplastic deformation behavior. This paper is concerned with the study of the microstructure and superplastic deformation behavior, with the construction of a constitutive model, of Al-Mg-Zn-Cu-Zr aluminum alloys with varying Ni contents. The aluminum solid solution and coarse precipitates of the T(Mg32(Al,Zn)49 and Al3Ni second phases were formed in the studied alloy and Cu dissolved in both second phases. The deformation behavior was investigated in the temperature range of 400–480 °C and the strain rate range of 10−3–10−1 s−1. Due to the fine Al3Zr precipitates, the alloys exhibit a partially recrystallized grain structure before the onset of superplastic deformation. Coarse precipitates of the second phases facilitate dynamic recrystallization and enhance superplasticity at the strain rates and temperatures studied. The alloys with ~6–9% particles exhibit high-strain-rate superplasticity at temperatures of 440–480 °C and strain rates of 10−2–10−1 s−1. The presence of high fractions of ~9% Al3(Ni,Cu) and ~3% T-phase precipitates provided high-strain-rate superplasticity with elongations of 700–800% at a low temperature of 400 °C. An Arrhenius-type constitutive model with good agreement between the predicted and experimental flow stresses was developed for the alloys with different Ni contents.